PENGARUH PEMBERIAN PAKAN KONSENTRAT DAN UREA MOLASES BLOK (UMB) TERHADAP PERTAMBAHAN BERAT BADAN SAPI POTONG - Nurwahidah J; A. L. Tolleng; Muhammad Nur Hidayat (Jurnal Ilmu dan Industri Peternakan, 2015)
ABSTRACT. This study aims to know the effect of concentrate and UMB woof giving on cow body weight increase. the research method is based 2 treatments, first treatment is UMB woof giving and second treatment is concentrate woof giving. Each treatments are based of 5 cows. Data were analyzed by T test (t- Test Independent Sample). Based on the results of analysis showed that effect of UMB and concentrate woof giving does not affect to body weight increase of cows.